Correlation between mother’s demand and cesarean section delivery in Pku Muhammadiyah Hospital Bantul Yogyakarta - Mastina Mastina; Herlin Fitriani Kurniawati (Universitas 'Aisyiyah Yogyakarta, 2019)
World Health Organization (WHO) found the number of Cesarean Section delivery in the world at 25.7% in 2004-2008 which was 27.3% in Asia, 19.0% in Europe, 29.2% in Latin America and the highest number was in China at the rate of 46.2% (Wang, Hellerstein, Hou, Zou, Ruan, Zhang, 2017). Rates determined by WHO for each country were 10-15% (WHO, 2015). WHO (2015) stated that the causative factor that can be delivered by Cesarean section is when vaginal delivery may have a risk to the mother and baby such as taking too much time for delivery and fetal disorders. Another cause was because of abnormal position. This study aims to determine the relationship between mother’s demand and Cesarean section delivery at PKU Muhammadiyah Hospital Bantul. The type of research used in this study is quantitative research with Cross Sectional approach using secondary data, namely medical record data of PKU Muhammadiyah Hospital Bantul in 2017. Chi-Square with P value 0.05 and CI 95% was used as data analysis. The bivariate results obtained were mother’s demand associated with delivery of Cesarean section with p value of 0.000 which means that the mother's demand had a significant relationship with the section Cesarean delivery. Based on the analysis of health technology assessment (HTA), the selection efforts at Cesarean section delivery were very beneficial for the mother and family, in terms of maternal health, economy and other factors.